THE ROLE OF OPERATING COMPANIES OPERATING IN THE IRAQI OIL SECTOR IN ADDRESSING THE PROBLEM OF UNEMPLOYMENT FOR THE PERIOD (2004-2020) - Adeeb Gassim Shandi; Alyaa Suhail Najm (Scholar Express Journals, 2023)
The Iraqi economy has great material and human capabilities that give it the ability to grow, progress and eliminate unemployment, but these capabilities and capabilities were not employed through a sound economic policy. As one of the most prominent justifications of the Iraqi government in bringing major international companies to work in the Iraqi oil sector is working to provide many job opportunities for the people of this country in addition to developing and training Iraqi cadres working in the oil sector, which reduces the unemployment rate in the country as well as contributing to the absorption of The high population growth that characterizes Iraq and the weakness of the productive sectors, and work to find solutions to this phenomenon and its economic, social and security repercussions. The research aims to know the reality of unemployment in Iraq for the period from 2004-2020. As well as knowing the reasons behind the increase in its rates in Iraq, as well as developing some proposed solutions to avoid the effects of unemployment. The research is based on one of its hypotheses that the phenomenon of unemployment in the oil sector is represented by a certain segment of human resources with low efficiency
Keywords: Iraqi economy; unemployment; oil